OPERATIONAL RISK ANALYSIS OF COMBINED CYCLE POWER PLANT TANJUNG PRIOK - Rachman Wijaya, Fauzi
The development of electricity is important in developing country like, Indonesia. Mostly in Indonesia the development of electricity is centralized in Java-Bali region. On that account, the electricity supply for Java-Bali region is important as it represents most of PT PLN’s customer. Consequently, a slightly disruption in electricity supply within Java-Bali region can be fatal or intolerable and on that account, needs to be averted. Therefore, Combined Cycle Power Plant Tanjung Priok as one of main power plant within Java-Bali region needs to understand and analyze the operational risks that later may affect the electricity supply within Java-Bali region. Risk Analysis in this research has been done by following risk management process based on ISO 31000: 2009 about risk management. Risk management process based on ISO 31000:2009 mainly consists of risk identification, risk analysis, risk evaluation, and risk mitigation. On that account, the process of this research mainly following those 4 steps. The process started by identifies risk factors which affected the operational process of Combined Cycle Power Plant Tanjung Priok by using Cause Code Data from management of power plant, then analyzing it in order to classify each risk factor into suitable categories for the risk matrix. The analyzing process done by using divided normal probability distribution approach which generated by using Monte Carlo Simulation. Then the result from Monte Carlo Simulation was analyzed further into risk matrix. Risk matrix itself becomes the main guidance in order to mitigate those risk factors. In the conclusion, this research provides mitigation for operational risk factors which affected Combined Cycle Power Plant Tanjung Priok and several recommendations for Combined Cycle Power Plant Tanjung Priok.